Building Teacher Literacy Culture in Vocational Schools: a Case Study of the SAKA Guru Program at The Vocational High School Level - Weny Fibrianti; Alip Sugianto; Sutrisno Sutrisno (Borneo Research and Education Center, 2026)
Despite the extensive proliferation of the School Literacy Movement, current operational paradigms remain predominantly student-oriented, thereby failing to substantively position teachers as primary agents of literacy production, particularly within the purview of vocational education. This study aims to describe the implementation, the supporting and inhibiting factors, and the impact of the SAKA Guru Program (One Teacher One Literary Work) in holistically building teacher literacy culture at SMK Negeri 1 Ponorogo. Adopting a qualitative approach with a case study design, empirical data were harvested via semi-structured interviews, participant observation, and documentary analysis utilizing six key informants. The data were analyzed using Braun and Clarke's thematic analysis through six stages: data familiarization, generating initial codes, searching for themes, reviewing themes, defining themes, and producing the research report; their validity was strengthened through source triangulation, method triangulation, and member checking. The empirical findings delineate three primary insights. First, the program's implementation produced a work-production-based teacher literacy model that positions teachers as the principal actors in the transformation of vocational literacy culture. Second, the program's success and sustainability were determined by the balance between systemic supporting factors (leadership support, facilities, training, a sharing culture, and appreciation) and inhibiting factors rooted in individuals and time constraints. Third, the program's impact emerged through a cycle of participation, work production, strengthening of professional identity, and replication of literacy culture, thereby encouraging the creation of literary works, reinforcing reading and writing habits, and cultivating a literacy culture among teachers. This study advances the theoretical paradigms of literacy as a social practice and the School Literacy Movement by translating these concepts into the realm of vocational teachers, while concurrently offering a holistic, teacher-centered literacy implementation model with teachers as producers of works that can be effectively replicated within analogous vocational contexts.